High Dose, Prolonged Epsilon Aminocaproic Acid Infusion, and Recombinant Factor VII for Massive Postoperative Retroperitoneal Hemorrhage following Splenectomy - Alex T. Lee; Christopher R. Barnes; Shweta Jain; Ronald Pauldine (Case Reports in Anesthesiology)
The antifibrinolytic agent ε-aminocaproic acid is used to decrease procedural blood loss in a variety of high risk surgeries. The utility of recombinant factor VII administration in massive hemorrhage has also been reported in a variety of settings, though the impact in a surgical context remains unclear. We describe the case of a patient who underwent massive open splenectomy and developed diffuse retroperitoneal bleeding on postoperative day one. Massive transfusion was initiated, but attempts to control hemorrhage with surgical and interventional radiology approaches were unsuccessful, as was recombinant factor VII administration. Commencement of a high dose aminocaproic acid infusion was followed by a prominent rise in fibrinogen levels and stabilization of the hemorrhage. Indications, dosages, and adverse effects of ε-aminocaproic acid as described in the literature are reviewed.